2019
DOI: 10.1016/j.nicl.2019.101807
|View full text |Cite
|
Sign up to set email alerts
|

Functional reorganization of neural networks involved in emotion regulation following trauma therapy for complex trauma disorders

Abstract: Objectives We investigated whether patients with complex interpersonal trauma engage neural networks that are commonly activated during cognitive reappraisal and responding naturally to affect-laden images. In this naturalistic study, we examined whether trauma treatment not only reduces symptoms but also changes neural networks involved in emotional control. Methods Before and after eight weeks of phase-oriented inpatient trauma treatment, patients ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 132 publications
5
46
0
Order By: Relevance
“…This is an essential prerequisite for the integration of trauma memories and development of a cooperative relationship with other dissociative parts (i.e., EPs; Nijenhuis, 2015Nijenhuis, , 2017Van der Hart et al, 2006). Thus, our results might reflect a remarkable therapeutic achievement and are in line with our previously published emotion regulation functional connectivity study (Schlumpf et al, 2019) showing that patients as ANP were less depersonalized, derealized, and emotionally numbed following phase-oriented treatment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is an essential prerequisite for the integration of trauma memories and development of a cooperative relationship with other dissociative parts (i.e., EPs; Nijenhuis, 2015Nijenhuis, , 2017Van der Hart et al, 2006). Thus, our results might reflect a remarkable therapeutic achievement and are in line with our previously published emotion regulation functional connectivity study (Schlumpf et al, 2019) showing that patients as ANP were less depersonalized, derealized, and emotionally numbed following phase-oriented treatment.…”
Section: Discussionsupporting
confidence: 91%
“…This hypothesis is only subordinate as we do not have a control group that was presented emotionally neutral pictures only. However, it is in line with our previous EEG functional connectivity emotion regulation study (Schlumpf et al, 2019) and fMRI investigations of exposure-based treatment effects on functional networks in PTSD patients at rest (Shou et al, 2017;Zhu et al, 2018) and during confrontation with reminders of traumatic events (Cisler et al, 2014;Helpman et al, 2016).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, in the case of DID, differential identity reactivity on (neuro)physiological measures may be driven by their self-understanding of harbouring multiple identities. This explanation may also account for the studies on neurophysiological and behavioural reactions to subliminally presented neutral and angry faces (Schlumpf et al, 2013(Schlumpf et al, , 2014Schlumpf, Nijenhuis, Klein, Jäncke, & Bachmann, 2019) with an equivalent line of reasoning. The explanation also fits perfectly well with our conceptualization of DID in terms of erroneous meta-cognitive understanding of the self as being composed of multiple identities and erroneous meta-memory processes including the belief of amnesic barriers between these identities.…”
mentioning
confidence: 89%
“…Researchers have studied the immediate and long-term results of complex trauma, both biologically and behaviorally. While the neural basis of these abnormalities has not been fully elucidated, previous studies have suggested an association between childhood trauma and structural and functional abnormalities of brain regions mediating emotion, such as the hippocampus, amygdala, and prefrontal cortex [19][20][21][22]. However, there are limitations in population studies, because inducing trauma to humans has ethical issues and because it is difficult to carry out well-validated behavioral and psychophysiological studies in human populations.…”
Section: Introductionmentioning
confidence: 99%